Baburids Hunting (Shikar) Ceremonies in the Context of Turkish Cultural Codes - Vedat Meral (Avrasya İncelemeleri Dergisi)
The historical practice of hunting traces its origins to the beginning of human civilization. Initially, hunting served as a means of survival for early humans, gradually evolving into a source of raw materials essential for various products during the Stone Age. Over time, hunting methods and tools have undergonetransformation and development. What was once a necessity for survival eventually evolved into a cultural tradition deeply ingrained in the fabric of almost every society. Within this historical context, hunting, known as “shikar,” emerged as a significant cultural element among the Turks, enduring the ages to the present day. Notably, it held a significant position in the traditions of the Mughal Empire, which ruled over India. Much like in other Turkish states, Mughal sultans actively organized and participated in hunting excursions. For the Mughals, hunting held a dual significance, serving as both a cherished pastime for sultans, mirzas, and members of the dynasty and as a crucial element of military training, ensuring soldier’s constant readiness for warfare. In addition, hunting often fulfilled practical purposes, ranging from satisfying food needs through hunting feasts to capturing and taming wild animals such as elephants for deployment in battles. Consequently, this study provides insights into hunting ceremonies as an integral part of Turkish culture, focusing on the Mughals as a representative example. This study aims to contribute valuable knowledge to the area of scholarly research in this field.